Stratigrafi Daerah Monano, Kabupaten Gorontalo Utara - Noho, Fitria Maharani Putri Iwan; Maryati, Sri; Kasim, Muhammad (Universitas Negeri Gorontalo, 2025)
The research is located in Gorontalo Province located between 0°48'0”- 0°58'0” N and 122°36'0” - 122°44'0” E. The location of this research is in Monano District, North Gorontalo Regency, Gorontalo Province. This geological mapping aims to map the geological conditions of the research area. The methods used are field surveys and spatial data analysis. Based on geomorphological data, 4 units were obtained in the form of Volcanic Hills Units, Denudational Hills Units, Marine Plains Units, Fluvial Plains Units. On the geological map, the lithology of the research area consists of andesite, agglomerate, sandstone alluvial sediment units. The results of the lineament density consist of 3 density classes, namely low, medium and high.